Implementing the Creating Learning Environments for Compassionate Care (CLECC) programme in acute hospital settings: a pilot RCT and feasibility study - Jackie Bridges; Ruth M Pickering; Hannah Barker; Rosemary Chable; Alison Fuller; Lisa Gould; Paula Libberton; Ines Mesa-Eguiagaray; James Raftery; Avan Aihie Sayer; Greta Westwood; Wendy Wigley; et al. (National Institute for Health Research, 2018)
Background: Concerns about the degree of compassion in health care have become a focus for national and international attention. However, existing research on compassionate care interventions provides scant evidence of effectiveness or the contexts in which effectiveness is achievable. Objectives: To assess the feasibility of implementing the Creating Learning Environments for Compassionate Care (CLECC) programme in acute hospital settings and to evaluate its impact on patient care. Design: Pilot cluster randomised trial (CRT) and associated process and economic evaluations. Setting: Six inpatient ward nursing teams (clusters) in two English NHS hospitals randomised to intervention (n = 4) or control (n = 2). Participants: Patients (n = 639), staff (n = 211) and visitors (n = 188). Intervention: CLECC is a workplace educational intervention focused on developing sustainable leadership and work team practices (dialogue, reflective learning, mutual support) theorised to support the delivery of compassionate care. The control setting involved no planned staff team-based educational activity. Main outcome measures: Quality of Interaction Schedule (QuIS) for staff-patient interactions, patient-reported evaluations of emotional care in hospital (PEECH) and nurse-reported empathy (as assessed via the Jefferson Scale of Empathy). Data sources: Structured observations of staff-patient interactions; patient, visitor and staff questionnaires and qualitative interviews; and qualitative observations of CLECC activities. Results: The pilot CRT proceeded as planned and randomisation was acceptable to teams. There was evidence of potential contamination between wards in the same hospital. QuIS performed well, achieving a 93% recruitment rate, with 25% of the patient sample cognitively impaired. At follow-up there were more positive (78% vs. 74%) and fewer negative (8% vs. 11%) QuIS ratings for intervention wards than for control wards. In total, 63% of intervention ward patients achieved the lowest possible (i.e. more negative) scores on the PEECH connection subscale, compared with 79% of control group patients. These differences, although supported by the qualitative findings, are not statistically significant. No statistically significant differences in nursing empathy were observed, although response rates to staff questionnaire were low (36%). Process evaluation: the CLECC intervention is feasible to implement in practice with medical and surgical nursing teams in acute care hospitals. Strong evidence of good staff participation was found in some CLECC activities and staff reported benefits throughout its introductory period and beyond. Further impact and sustainability were limited by the focus on changing ward team behaviours rather than wider system restructuring. Economic evaluation: the costs associated with using CLECC were identified and it is recommend that an impact inventory be used in any future study. Limitations: Findings are not generalisable outside hospital nursing teams, and this feasibility work is not powered to detect differences attributable to the CLECC intervention. Conclusions: Use of the experimental methods is feasible. The use of structured observation of staff-patient interaction quality is a promising primary outcome that is inclusive of patient groups often excluded from research, but further validation is required. Further development of the CLECC intervention should focus on ensuring that it is adequately supported by resources, norms and relationships in the wider system by, for instance, improving the cognitive participation of senior nurse managers. Funding is being sought for a more definitive evaluation. Trial registration: Current Controlled Trials ISRCTN16789770. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 6, No. 33. See the NIHR Journals Library website for further project information. The systematic review reported in Chapter 2 was funded by the NIHR Collaboration for Leadership in Applied Health Research and Care Wessex, the University of Örebro and the Karolinska Institutet.